INTEGRATING ISLAMIC PARENTING PRACTICES INTO URBAN CONTEXTS: A TAFSIR TARBAWI APPROACH - Ariyadi, Samsul (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the effectiveness of Islamic parenting practices in urban modern contexts by employing a tafsir tarbawi approach in the interpretation of Qur’anic passages. Utilizing a qualitative methodology based on a comprehensive literature review of Scopus-indexed journals from 2019 to 2024, the research integrates attachment parenting theory with traditional Islamic educational (tarbiyah) principles. Focusing on major Indonesian cities where the Muslim population is dominant, the study reveals the challenges of implementing Islamic parenting amidst the complexities of urban digital culture and extraneous socio-economic pressures. Through structured analysis following the IMRAD format, this paper outlines practical frameworks for integrating Islamic parenting values in urban settings and delineates actionable strategies for educators, policymakers, and community leaders. The findings contribute to the academic discourse on Islamic education and modern parenting by proposing an integrative model that bridges classical theological interpretation with contemporary attachment research.